External Validation of a Predictive Model of Urethral Strictures for Prostate Patients Treated With HDR Brachytherapy Boost - Panettieri, Vanessa; Rancati, Tiziana; Onjukka, Eva; Ebert, Martin A.; Joseph, David J.; Denham, James W.; Steigler, Allison; Millar, Jeremy L. (Frontiers in Oncology, 2020)
Purpose:For prostate cancer treatment, comparable or superior biochemical control was reported when using External-Beam-Radiotherapy(EBRT) with High-Dose-Rate-Brachytherapy(HDRB)-boost, compared to dose-escalation with EBRT alone. The conformal doses produced by HDRB could allow further beneficial prostate dose-escalation, but increase in dose is limited by normal tissue toxicity. Previous works showed correlation between urethral dose and incidence of urinary toxicity, but there is a lack of established guidelines on the dose constraints to this organ. This work aimed at fitting a Normal-Tissue-Complication-Probability model to urethral stricture data collected at one institution and validating it with an external cohort, looking at neo-adjuvant androgen deprivation as dose-modifying factor. Materials/Methods:Clinical and dosimetric data of 258 patients, with a toxicity rate of 12.8%, treated at a single institution with a variety of prescription doses, were collected to fit the Lyman-Kutcher-Burman(LKB) model using the maximum likelihood method. Due to the different fractionations, doses were converted into 2Gy-equivalent doses (α/β =5Gy), and urethral stricture was used as an end-point. For validation an external cohort of 187 patients treated as part of the TROG(Trans-Tasman-Radiation-Oncology-Group)03.04RADAR trial with a toxicity rate of 8.7%, was used. The goodness of fit was assessed using calibration plots. The effect of neo-adjuvant androgen deprivation(AD) was analysed separating patients who had received it prior to treatment from those who did not receive it. Results:The obtained LKB parameters were TD50=116.7Gy and m=0.23; n was fixed to 0.3, based on numerical optimisation of the likelihood. The calibration plot showed a good agreement between the observed toxicity and the probability predicted by the model, confirmed by bootstrapping. For the external validation the calibration plot showed that the observed toxicity obtained with the RADAR patients was well represented by the fitted LKB model parameters. When patients were stratified by the use of AD TD50 decreased when AD was not present. Conclusions:Lyman-Kutcher-Burman model parameters were fitted to the risk of urethral stricture and externally validated with an independent cohort, to provide guidance on urethral tolerance doses for patients treated with a HDRB boost. For patients that did not receive AD, model fitting provided a lower TD50 suggesting a protective effect on urethra toxicity.